Densities, viscosities, volumetric properties and intermolecular interactions of binary mixtures of 1-ethyl-2, 3-dimethylimidazolium tetrafluoroborate with three solvents. (January 2023) - Han, Jingli; Li, Manxing; Wang, Haobing; Zhang, Yingying; Tian, Junfeng; Yang, Xuzhao
Graphical abstract: Highlights: Binary mixtures of [EDMIM][BF4 ] with methanol, acetonitrile and acetone were studied. Densities, viscosities and volumetric properties have been obtained and discussed. The Pitzer model and the Erying dynamic equation were used to fit the properties. The interaction mechanism was analyzed at the molecular level by the COSMO-RS model. Abstract: Densities and viscosities of binary mixtures of 1-ethyl-2, 3-dimethylimidazolium tetrafluoroborate [EDMIM][BF4 ] with methanol, acetonitrile and acetone at 293.15 to 333.15 K were studied in this work. Volumetric properties including the apparent molar volume, the excess molar volume, the partial molar volume and the excess partial molar volume were calculated from the density data. The empirical linear formula was used to correlate the densities of the binary systems, and the apparent molar volumes and the viscosity were fitted with the Pitzer model and the Erying dynamic equation, respectively. Finally, the COSMO-RS model was adopted to analyze the interaction mechanism at the molecular level.